Social media use and social anxiety symptoms : the role of fear of missing out and social comparison - Súsanna Ísabella Jóhannsdóttir 1999- (2022)
With the drastic augment in social media usage in recent years, researchers have begun to wonder how it might affect social anxiety symptoms. Recent studies suggest that the association between social media use and social anxiety symptoms may be mediated by fear of missing out (FoMO) and social comparison (SC); however, research on this is scarce. This study aimed to investigate whether social media use affects social anxiety symptoms and whether FoMO and SC mediate the connection between social media usage and social anxiety symptoms. Participants in the study were university students aged 18 to 30 years old (N = 87). Participants completed an online survey regarding time spent on social media, social anxiety symptoms, FoMO, and SC on the online platform SurveyMonkey. Analyses included linear regression and the PROCESS Macro to test mediation. Results showed a trend in the association between social media use and social anxiety symptoms (p-value = 0.08). However, FoMO and SC mediated the relationship between time spent on social media and social anxiety symptoms. To our knowledge, this was the first study of its kind conducted in Iceland so far. The study’s limitations included a small sample size and the length of completing the measure. Keywords: social media use, social anxiety symptoms, well-being, fear of missing out, social comparison Mikil aukning hefur verið á notkun samfélagsmiðla á undanförnum árum. Út frá því hafa vísindamenn velt því fyrir sér hvernig samfélagsmiðlar geta haft áhrif á einkenni félagskvíða. Nýlegar rannsóknir hafa gefið tilkynna að tengsl milli samfélagsmiðlanotkunar og félagskvíðaeinkenna sé miðlað af útundanótta og félagslegum samanburði, þó eru rannsóknir af þessu tagi af skornum skammti. Þessi rannsókn miðaði að því að rannsaka hvort samfélagsmiðlanotkun hafi áhrif á einkenni félagskvíða og hvort útundanótti og félagslegur samanburður miðli áhrifin milli samfélagsmiðlanotkunar og félagskvíðaeinkenna. Þátttakendur þessarar rannsóknar voru háskólanemar á aldrinum 18 til 30 ára (N ...